Effect of different contents of organic-inorganic hybrid particles poly(methyl methacrylate)ZrO2 on the properties of poly(vinylidene fluoride-hexafluoroprolene)-based composite gel polymer electrolytes. (10th May 2018) - Wang, Zhiyan; Miao, Chang; Xiao, Wei; Zhang, Yan; Mei, Ping; Yan, Xuemin; Jiang, Yu; Tian, Minglei
Abstract: Poly(vinylidene fluoride-hexafluoroprolene) (P(VDF-HFP))-based composite polymer electrolyte (CPE) membranes doped with organic-inorganic hybrid particles poly(methyl methacrylate)ZrO2 (PMMA-ZrO2 ) are fabricated by phase inversion, in which PMMA is firstly successfully grafted onto the surface of the homemade nano-ZrO2 particles via in situ polymerization confirmed by FT-IR. XRD and DSC patterns show that adding PMMA-ZrO2 into the polymer matrix can decrease the crystallinity of the CPE membranes and TG curves indicate the CPE membranes possess desirable thermal stability. It can be found that the CPE membrane presents a uniform surface with abundant interconnected micro-pores when the added amount of PMMA-ZrO2 increases to 5 wt % vs . polymer matrix, in which the ionic conductivity at room temperature and tensile strength can be up to 3.595 mS cm −1 and 26.18 MPa, respectively. In particular, the CPE membrane shows the minimum deformation of about 8% after being exposed at 160 °C for 1 h, and the electrochemical working window of the assembled Li/CPE/SS cell can be stable at 5.1 V ( vs Li/Li + ) at room temperature. Moreover, the LiCoO2 /CPE/Li coin cell can deliver a specific capacity of 114.5 mAh g −1 with 79.13% capacity retention at 2.0 C after 110 cycles. The results suggest that the as-fabricated P(VDF-HFP)-based CPE doped with 5 wt % organic-inorganic hybrid particles PMMA-ZrO2 can be a promising polymer electrolyte for lithium ion batteries. Graphical abstract: Coulombic efficiency and cycle plots of the LiCoO2 /CPE-5/Li coin cell at different rates, the inserts are SEM images of the CPE membranes and the digital photos of the CPE- x membranes ( x = 0, 3, 5 and 8 wt %) before (A) and after (B) thermal exposure at 160 °C for 1 h. Highlights: Organic-inorganic hybrid particles PMMA-ZrO2 are synthesized via in situ polymerization. The ionic conductivity and tensile strength of the CPE-5 is up to 3.595 mS cm −1 and 26.18 Mpa, respectively. The CPE-5 membranes show the minimum deformation after being exposed at 160 °C for 1 h. The assembled cells show good rate and cycle performance.